2017
DOI: 10.1080/10833196.2017.1287151
|View full text |Cite
|
Sign up to set email alerts
|

Methodological consistency and measurement reliability of transversus abdominis real time ultrasound imaging in chronic low back pain populations: a systematic review

Abstract: Bac kgr o und:Real tim e ultrasound im aging (RTUI) is used to m easure transversus abdom inis (TrA) thickness in low back pain (LBP ) populations. However, individuals with chronic low back pain (C LBP ) pose specific im aging challenges, such as older age and higher body m ass index, com pared to asym ptom atic populations or acute and sub-acute LBP groups. These challenges potentially increase m easurem ent error and m ay require different im aging m ethods. O bje c t ive s :This review describes the m etho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
9
0

Year Published

2018
2018
2019
2019

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(9 citation statements)
references
References 50 publications
0
9
0
Order By: Relevance
“…However, there is no external means of controlling probe-patient pressure, inclination (side to side tilt), and roll (forward and backward tilt) using this method, leading to variability in these probe parameters. This constitutes a potential source of TrA measurement error, [16][17][18] and theoretically reduces the reliability of US TrA measurement by clinicians and researchers, because a clinical measurement must be reliable if it is to be useful. 16 Costa et al 16 and Whittle et al 18 suggested that reliability of TrA measurement using US in both healthy and LBP groups has been suboptimal due to poor study designs and a lack of standardization of imaging procedures.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…However, there is no external means of controlling probe-patient pressure, inclination (side to side tilt), and roll (forward and backward tilt) using this method, leading to variability in these probe parameters. This constitutes a potential source of TrA measurement error, [16][17][18] and theoretically reduces the reliability of US TrA measurement by clinicians and researchers, because a clinical measurement must be reliable if it is to be useful. 16 Costa et al 16 and Whittle et al 18 suggested that reliability of TrA measurement using US in both healthy and LBP groups has been suboptimal due to poor study designs and a lack of standardization of imaging procedures.…”
Section: Introductionmentioning
confidence: 99%
“…This constitutes a potential source of TrA measurement error, [16][17][18] and theoretically reduces the reliability of US TrA measurement by clinicians and researchers, because a clinical measurement must be reliable if it is to be useful. 16 Costa et al 16 and Whittle et al 18 suggested that reliability of TrA measurement using US in both healthy and LBP groups has been suboptimal due to poor study designs and a lack of standardization of imaging procedures. Measurement of TrA-C has demonstrated the lowest reliability when compared to resting thickness of the transverse abdominis (RTrA) and contracted thickness of the transverse abdominis (CTrA), and only a few studies have reported reliability of TrA-C, despite its clinical importance.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Some studies have demonstrated TrA-C anomalies, 4 TrA morphological changes 5 and the efficacy of some therapeutic interventions to improve TrA-C. 6 Notwithstanding, US TrA-C measurement in CLBP populations has been characterized by widely variable and generally suboptimal intra-observer reliability. 7 Only two prior studies have reported intra-observer TrA-C measurement reliability in CLBP. 3,8 Reliability was suboptimal (intra-class correlation coefficient (ICC) ¼ 0.32-0.72).…”
Section: Introductionmentioning
confidence: 99%
“…3,8 Reliability was suboptimal (intra-class correlation coefficient (ICC) ¼ 0.32-0.72). 7 Such variability has been considered solely dependent upon the failed application of rigorous application protocols, 9 yet a consensus regarding such protocols is currently lacking and is problematic given that US is a 'freehand' procedure. 7 Methodological deficiencies inherent with 'freehand' US are uncontrolled probe force (amount of pressure applied to the patients skin), inclination (side-to-side tilt of the probe perpendicular to the plane of the probe) and roll (forward and backward movement parallel to the scan plane of the probe).…”
Section: Introductionmentioning
confidence: 99%